THE APPLICATION OF LAW IN DETERMINING THE AUTHORITY BETWEEN THE CENTRAL AND LOCAL GOVERNMENTS IN UPSTREAM OIL AND GAS PROJECTS IN INDONESIA - Putra, Rizki Dwi; Sinlae, Ester Stevany Putri; syahda, Illa fatika; syifa, Tazkia suhaila; Insan, Isep H (Universitas Labuhanbatu, 2025)
In Indonesia, the regulation of oil and gas affairs is an important focus regarding the division of authority between the central and local governments. The central government has control over national policies and contracts, while local governments are responsible for local planning and tax revenue. Disputes often arise over royalties, taxes and environmental responsibilities. The solution lies in solid cooperation between the two parties, ensuring that both national and local interests are met fairly. With this collaborative approach, Indonesia can derive optimal benefits from the oil and gas sector while being mindful of sustainability and shared prosperity.Keywords: Oil and Gas, Division of authority, Governance